2020
DOI: 10.1088/1674-1137/abb4d4
|View full text |Cite
|
Sign up to set email alerts
|

Description of alpha-clustering of 8Be nucleus states in high-precision theoretical approach

Abstract: Scrupulous theoretical study of 8Be nucleus states, both clustered and non-clustered, is performed over a wide range of excitation energies. The quantities that characterize the degree of the alpha-clustering of these states, i.e., spectroscopic factors, cluster form factors, and alpha-decay widths, are computed in the framework of the developed accurate ab initio approach. Other basic properties of the 8Be spectrum, including the binding and excitation energies and the mean values of the isospin, are calculat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…In our previous works [45][46][47], it was shown that even a not too large deviation of the calculated resonance energy from the experimental one leads to a noticeable change in the calculated value of the decay width. For this reason, the use of experimental resonance energies in calculating decay widths is preferable.…”
Section: Outline Of Methodology Of the Approachmentioning
confidence: 90%
See 2 more Smart Citations
“…In our previous works [45][46][47], it was shown that even a not too large deviation of the calculated resonance energy from the experimental one leads to a noticeable change in the calculated value of the decay width. For this reason, the use of experimental resonance energies in calculating decay widths is preferable.…”
Section: Outline Of Methodology Of the Approachmentioning
confidence: 90%
“…In our previous papers [45][46][47], an ab initio approach was developed. It allows one to calculate the asymptotic characteristics of the real decay of unbound and virtual splitting of bound states of nuclei namely the total and partial decay widths and the asymptotic normalization coefficients (ANCs) of certain channels, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in the recent calculations with the Daejon16 N N interaction in Ref. [20] the energy of the intruder 0 + is shown to drop to 11.71 MeV in the largest model space with Ω =15 MeV. The study also calculated the widths of the 0 + and 2 + states to be 8.86 MeV and 3.57 MeV, respectively, using NCSM combined with the resonating group method (RGM).…”
Section: LI Beta Decaymentioning
confidence: 93%
“…In addition, a recent experimental study has found a tentative evidence for a broad 0 + state at 12 MeV, prompting a need for further measurements [17]. Various earlier ab initio studies have seen intruder 0 + and 2 + states as well [18][19][20]. In particular, the extrapolations in the earlier study in Ref.…”
Section: LI Beta Decaymentioning
confidence: 94%